The Practicality of Interactive Learning Media Based on Android Applications in the Concept of Human Respiratory System for High School - Candra Pratama b; Kaspul Kaspul; Muhammad Arsyad (International Journal of Regional Innovation, 2022)
An important source of learning in the millennial era is interactive learning media that can be accessed via smartphones. Development research that produces a practical Android learning media. This type of research was adapted from Tessmer's design, through initial preparation (preparation) and formative evaluation (formative evaluation). The practicality of the contents of 5 students of class XI MIPA 2 through individual tests. The subject of practicality is the expectation of 9 students of Class XI MIPA 2 through a small group test. Data obtained from research instruments consisted practicality of contents, and practicality of expectations. The technique of approving data uses approved sheets. Practicality based on the Akbar & Sriwiyana category (2010). This media obtained practicality of contents 88.00%, and practicality of expectations 96.30%, so that it was included in the category of very practical